Refractory Celiac Disease Type II: A Case Report that Demonstrates the Diagnostic and Therapeutic Challenges - Fernandes,Alexandra (2016)
Refractory celiac disease is an uncommon but serious complication of celiac disease. We describe a case of a severe refractory celiac disease type II, complicated with ulcerative jejunoileitis, in a 68 years old female, unresponsive to consecutive treatments with budesonide, prednisolone, cladribine and autologous stem cell transplantation. The patient maintained severe malnutrition, advanced osteoporosis, anaemia, vitamin deficiencies and hydro-electrolytic imbalances, necessitating consecutive hospitalizations for total parenteral nutrition. The patient also developed life-threatening complications, namely respiratory and urinary septic shock and also episodes of haemorrhagic shock secondary to ulcerative jejunoileitis. The progression to enteropathy associated T-cell lymphoma was never demonstrated, but the patient died 7 years after the diagnosis due to a septic shock secondary to a nosocomial pneumonia and osteomyelitis related to a spontaneous hip fracture. This case highlights the difficulties in the diagnostic process, therapeutic management and surveillance of this rare condition associated with very poor prognosis.